Color Processing in Zebrafish Retina - Meier, April; Nelson, Ralph; Connaughton, Victoria P. (Frontiers in Cellular Neuroscience, 2018)
Zebrafish (Danio rerio) is a model organism for vertebrate developmental processes and, through a variety of mutant and transgenic lines, various diseases and their complications. Some of these diseases relate to proper function of the visual system. In the US, the National Eye Institute indicates > 140 million people over the age of 40 have some form of visual impairment. The causes of the impairments range from refractive error to cataract, diabetic retinopathy, and glaucoma, plus heritable diseases such as retinitis pigmentosa and color vision deficits. Most impairments directly affect the retina, the nervous tissue at the back of the eye. Zebrafish with long or short-wavelength color blindness, altered retinal anatomy due to hyperglycemia, high intraocular pressure, and reduced pigment epithelium are all used, and directly applicable, to study how these symptoms affect visual function. However, many published reports describe only molecular/anatomical/structural changes or behavioral deficits. Recent work in zebrafish has documented physiological responses of the different cell types to colored (spectral) light stimuli, indicating a complex level of information processing and color vision in this species. The purpose of this review is to consolidate published morphological and physiological data from different cells to describe how zebrafish retina is capable of complex visual processing. This information is compared to findings in other vertebrates and relevance to disorders affecting color processing is discussed